(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The article studies methods and ways of increasing the efficiency of submersible pumps, as well as modernisation of structural elements of their control means to increase the efficiency and utilisation rate of pumping equipment using innovative technical solutions of Grundfos company.